2022
DOI: 10.1007/s10570-022-04997-6
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose-based films with internal plasticization with epoxidized soybean oil

Abstract: A process was developed combining two natural-based products to obtain bio-based films. Industrial cellulose pulp was dissolved and mixed with epoxidized soybean oil (ESBO), which acts as an internal plasticizer. A distillable and recyclable ionic liquid-based solvent was used to dissolve the cellulose. Appropriate distribution of the cellulose/ESBO solution on glass surfaces and careful regeneration of the cellulose enabled the development of solvent-free and flexible cellulose films. Fourier transform infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…A comparison of these FTIR spectra indicates that the characteristic CO absorption peak of the ester group was observed at 1736 cm –1 for cotton fibers treated with ESO and PHMG. This observation suggests the successful covalent bonding of ESO molecules to the cotton fibers . Notably, the absorption peak observed at 1640 cm –1 , assigned to the stretching vibration of the CN bonds, exhibited a substantial increase in intensity in the spectrum of the modified cotton fiber. , Furthermore, the stretching vibration peak of C–N bonds appearing at 1280 cm –1 overlapped with the stretching vibration peak of C–O bonds …”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…A comparison of these FTIR spectra indicates that the characteristic CO absorption peak of the ester group was observed at 1736 cm –1 for cotton fibers treated with ESO and PHMG. This observation suggests the successful covalent bonding of ESO molecules to the cotton fibers . Notably, the absorption peak observed at 1640 cm –1 , assigned to the stretching vibration of the CN bonds, exhibited a substantial increase in intensity in the spectrum of the modified cotton fiber. , Furthermore, the stretching vibration peak of C–N bonds appearing at 1280 cm –1 overlapped with the stretching vibration peak of C–O bonds …”
Section: Resultsmentioning
confidence: 83%
“…This observation suggests the successful covalent bonding of ESO molecules to the cotton fibers. 38 Notably, the absorption peak observed at 1640 cm −1 , assigned to the stretching vibration of the C�N bonds, exhibited a substantial increase in intensity in the spectrum of the modified cotton fiber. 39,40…”
Section: Characterization Of the Modified Cotton Fabrics 331 Ftir Spe...mentioning
confidence: 95%
“…For the ESO, a peak at 829 cm –1 can be observed that correlates with the presence of epoxy groups. Furthermore, peaks at 1690, 2930, and 2850 cm –1 are seen that are associated with the – CO stretching vibrations associated with the carboxyl group and the methyl and methylene – C–H stretching vibrations, respectively . In the FTIR spectrum of the polyol product, termed ER, a broad peak at 3490 cm –1 is observed.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, peaks at 1690, 2930, and 2850 cm −1 are seen that are associated with the − C�O stretching vibrations associated with the carboxyl group and the methyl and methylene − C−H stretching vibrations, respectively. 18 In the FTIR spectrum of the polyol product, termed ER, a broad peak at 3490 cm −1 is observed. This peak corresponds to the − OH stretching vibration, which indicates the occurrence of a ring-opening reaction between the epoxy group and the carboxyl group.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus far, numerous eco-friendly bio-based plasticizers have been studied and applied, such as epoxidized soybean oil, 32,33 epoxidized sunflower oil, 34,35 cashew phenol-based plasticizers, 36,37 sugar alcohol-based plasticizers, [38][39][40] citric acid-based plasticizers, 41,42 bio-based glycerol, 43 and so on. The agricultural and forestry by-products and their derivatives are the main monomer materials used in manufacturing these plasticizers.…”
Section: Introductionmentioning
confidence: 99%